Depression among the elderly people (Bangladesh Journal of Psychiatry, 2022)
Depression is a common but neglected psychological disorder among elderlies which have the potential of worsening the general health condition, thus is a considerable public health problem. The present study attempted to evaluate the status of depression among the elderlies in regard with socio-demographic background and the co-morbid conditions. With a cross sectional study design, this study was conducted in one of the area in Dhaka city during the period of January to December, 2019, among 175 elderly people aged e”60 years using convenient sampling technique. Depression among the respondents was evaluated with Bangla version of Geriatric Depression Scale-Short Form (GDS-SF Bangla version). Data regarding socio-demographic background and their co-morbidities had been collected. The results showed that, respondents with no depression was 46.9% where mild, moderate and severe level of depression was found in 26.9%, 12.6% and 13.7% of the respondents respectively. Being female and not having spouse found to make the elderlies more vulnerable to be suffering from depression (p